A Simple Approach to Investigate Intrahousehold Allocation of Private and Public Goods - Donni, Olivier (The Review of Economics and Statistics, 2009)
We adopt the collective approach to consumer behavior with egoistic agents and assume that household consumption is either private or public. We then show that (1) household demand functions have to satisfy testable constraints and (2) some elements of the decision process can be retrieved from observed behavior. These results are based on a conditional demand (m-demand) framework in which household demand functions are directly derived from the individual marginal rates of substitution. Finally, we present an empirical illustration of these theoretical results using the U.S. Consumer Expenditure Survey.